Magneto-plasma separation as a method for reprocessing of spent fuel and radioactive waste - Yegorov, A.M.; Skibenko, E.I.; Kovtun, Yu.V.; Yuferov, V.B. (Вопросы атомной науки и техники, 2008)
A variant of a separating device based on the plasma-beam discharge is considered, including: processes of radioactive material (SF and RAW) ionization; evaluation of the mass-production capacity of the device with taking into account the atomic weight of the separated substance and the spatial-density characteristics of the plasma used and main power consumption. The consideration enables one to estimate more objectively the potentialities of magneto-plasma separating devices and to determine the method for controlling them. Розглянуто варіант сепаруючого пристрою на основі пучково-плазмового розряду, у тому числі: процеси іонизації речовини ВЯП і РАВ; оцінка масової продуктивності пристрою з урахуванням атомної ваги виділюваної речовини і просторово-щільністних характеристик використовуваної плазми; оцінка основних енерговитрат. Проведений розгляд дозволяє більш предметно оцінити можливості магніто-плазмових сепараційних пристроїв і визначити спосіб їхнього регулювання. Рассмотрен вариант сепарирующего устройства на основе пучково-плазменного разряда, в том числе: процессы ионизации вещества ОЯТ и РАО; оценка массовой производительности устройства с учетом атомного веса выделяемого вещества и пространственно-плотностых характеристик используемой плазмы; оценка основных энергозатрат. Проведенное рассмотрение позволяет более предметно оценить возможности магнито-плазменных сепарационных устройств и определить способ их регулирования.